EXPERIMENTAL STUDY ON NATURAL, FORCED AND MIXED CONVECTION IN SUB-CHANNEL CYLINDERS HEXAGONALLY ARRAYED - FEBRIYANTO (NIM : 24908007); Tim Pembimbing : Prof. Dr. Aryadi Suwono; Dr. Nathanael P. Tandi, CATUR
Forced, natural and mixed convection in vertical cylinders bundels are transfer mechanism that widely used in many engineering applications. Examples of such applications are in heat exchanger, used nuclear fuel storage, and nuclear reactor core. For those applications, heat transfer correlations of forced, natural, and mixed convection flow in vertical rod bundles need to be developed. Several researches on heat transfer in vertical sub-channel between cylinders have been conducted, but only few researches in scope of flow condition low Reynolds numbers and thermally and/or hydro-dynamically developing flows. The numerical study has been conducted by Anggoro Septilarso. Both the numerical study and experimental study are using the same cylinders hexagonally arrayed. Then, the results of the experimental study will be compared with the results of numerical study. For flow condition on both studies are same, in which studies have been conducted on turbulent, natural and mixed convection by using water as cooling fluid through sub-channels formed within a hexagonal vertical rod bundle with P/D = 1,16 that is heated uniformly. In the experiment, all boundary layer of convection flows are developing (are not fully developed). The correlation equations of heat transfer developed on the experiment use diameter hydraulics. Reynolds number varies from 867 to 4911 and Graetz number varies from 143 to 3087 for forced convection flow. Rayleigh number varies from 95 x 10 6 to 2 x 10 9 for natural convection flow, and Richardson number varies from 2 to 77 and Graetz number varies from 143 to 3087 for mixed convection flow.